Implementation of Arabic Language Learning at Kanjeng Sepuh Sidayu Gresik Islamic Senior High School - Zahrotul Jannah, Rizka; Putri, Sinta Amalia; Rosikh, Fahrur; Rohman, M. Fathor (Funun Arabiyyah: Journal of Arabic Education and Literature, 2025)
This study aims to describe the implementation of Arabic language learning at MA Kanjeng Sepuh Sidayu Gresik, including the planning, implementation, and evaluation processes, as well as identifying supporting and inhibiting factors faced in the process. This study uses a descriptive qualitative approach with data collection techniques in the form of observation, in-depth interviews, and documentation. The subjects of the study consisted of Arabic teachers, students and vice principals of the madrasah. The results of the study indicate that Arabic language learning at MA Kanjeng Sepuh has been implemented in accordance with the curriculum structure, although it is still predominantly using conventional methods. The implementation of learning includes planning, implementation and evaluation activities. Learning using the vocabulary guessing game is very good. Supporting factors include the enthusiasm of teachers and students in learning Arabic as well as a conducive madrasah environment and support from the madrasah. Meanwhile, the obstacles faced include low student learning motivation, limited innovation in the use of communicative and contextual learning methods.